Comparative Study Between Mini PCNL and RIRS in the Treatment of Renal Stones (Bangladesh Journal of Urology, 2020)
Aim: The aim of this study is to compare the outcomes of miniaturized percutaneous nephrolithotomy (mini-perc) and retrograde intrarenal surgery (RIRS) in management of renal stones with a diameter